Experimental and meta-analytic evidence that source variability of misinformation does not increase eyewitness suggestibility independently of repetition of misinformation - O’Donnell, Rachel; Chan, Jason C. K.; Foster, Jeffrey L.; Garry, Maryanne (Frontiers in Psychology, 2023)
This work was adapted from the first author's master's thesis, which was written to fulfill the requirements of her master's degree during her Doctoral Program in Psychology at Iowa State University. R.O. and J.C. conceived the research idea, and R.O. collected and analyzed the data for both experiments under the guidance of J.C. R.O. wrote the full first draft of the manuscript, and J.C. provided revisions. M.G. and J.F. provided consultations on the project, suggestions regarding the design and procedure, and comments on the manuscript.